Systematic Coronary Risk Evaluation (SCORE): JACC Focus Seminar 4/8 - Graham, Ian M.; Di Angelantonio, Emanuele; Visseren, Frank; De Bacquer, Dirk; Ference, Brian A.; Timmis, Adam; Halle, Martin; Vardas, Panos; Huculeci, Radu; Cooney, Marie-Therese (Journal of the American College of Cardiology, 2021)
Clinical estimation of the combined effect of several risk factors is unreliable and this resulted in the development of a number of risk estimation systems to guide clinical practice. Here, after defining general principles of risk estimation, the authors describe the evolution of the European Society of Cardiology's (ESC) Systematic COronary Risk Evaluation (SCORE) risk estimation system and some learnings from the data. They move on to describe the establishment of the ESC's Cardiovascular Risk Collaboration and outline its proposed research directions. First among these is the evolution of SCORE 2, which provides updated, calibrated risk estimates for total cardiovascular events for low, moderate, high, and very high-risk regions of Europe. The authors conclude by considering that the future of risk estimation may be to express risk as years of exposure to a cardiovascular risk factor profile rather than risk over a fixed time period, such as 10 years, and how advances in genetics may permit individualized lifetime risk estimation from childhood on.
CRIS-Team Scopus Importer:2023-03-08
Keywords: cardiovascular disease; CVD risk assessment; Heart Score; prevention; risk assessment